Improving Pesantren Performance Through Transformational Leadership, Social Entrepreneurship, and Social Capital: The Mediating Roles of Creativity and Social Value Creation - Muhammad Hafidh Nashrullah; Sukesi; Slamet Riyadi; Nawari; Ahmad Munir Hamid (Global Research Collaboration, 2026)
This study examines how transformational leadership, social entrepreneurship, and social capital influence pesantren performance, both directly and indirectly through creativity and social value creation. A quantitative explanatory design was applied using a census of 217 respondents, consisting of 9 leaders and 208 employees of pesantren business units from nine pesantren in East Java, Indonesia. Data were analyzed using partial least squares structural equation modeling with SmartPLS 4.1. The structural model explained 61.2% of the variance in pesantren performance (R² = 0.612), 33.0% of the variance in social value creation (R² = 0.330), and 29.5% of the variance in creativity (R² = 0.295). The strongest direct effect was transformational leadership on social value creation (β = 0.424, p < 0.001), followed by social entrepreneurship on social value creation (β = 0.404, p < 0.001). Transformational leadership, social entrepreneurship, and social capital significantly increased creativity. Transformational leadership and social entrepreneurship also significantly increased social value creation, whereas social capital did not have a significant direct effect on social value creation (β = 0.075, p = 0.281). Pesantren performance was significantly influenced by transformational leadership, social entrepreneurship, social capital, creativity, and social value creation. Creativity significantly mediated the effects of transformational leadership (β = 0.072, p = 0.021), social entrepreneurship (β = 0.054, p = 0.033), and social capital (β = 0.065, p = 0.012) on pesantren performance. Social value creation mediated the effects of transformational leadership (β = 0.097, p = 0.001) and social entrepreneurship (β = 0.092, p = 0.004), but it did not mediate the relationship between social capital and performance (β = 0.017, p = 0.325). The findings show that pesantren performance is strengthened when leadership, entrepreneurial orientation, and relational resources are converted into creative organizational routines and measurable social value.